1990
DOI: 10.1136/jnnp.53.6.459
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of cases of Creutzfeldt-Jakob disease in England and Wales 1970-84.

Abstract: Two hundred and sixty seven patients with a definite or probable diagnosis of Creutzfeldt-Jakob disease (CJD) were identified in an attempt to ascertain all cases of the disease in England and Wales in the period 1970-84. No evidence of space-time clustering of dates and places of onset was found for these cases. Two age-and sex-matched controls were selected for 72 of the 122 cases diagnosed in the period 1980-84 and life histories of places of residence were obtained for these cases and the controls. No evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…The BSE epidemic has led to considerable concern about the safety for humans consuming beef and dairy products. Although epidemiologic studies over the past two decades argue that humans do not contract CJD from scrapie-infected sheep products (43)(44)(45), it is unknown whether any of the seven amino acid substitutions that distinguish bovine from sheep PrP render bovine prions permissive in humans (46). Whether Tg(MHu2M) mice are susceptible to bovine or sheep prions is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The BSE epidemic has led to considerable concern about the safety for humans consuming beef and dairy products. Although epidemiologic studies over the past two decades argue that humans do not contract CJD from scrapie-infected sheep products (43)(44)(45), it is unknown whether any of the seven amino acid substitutions that distinguish bovine from sheep PrP render bovine prions permissive in humans (46). Whether Tg(MHu2M) mice are susceptible to bovine or sheep prions is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Why have older individuals not developed vCJD-based neuropathologic criteria? It is noteworthy that epidemiological studies over the past three decades have failed to find evidence for transmission of sheep prions to humans (9)(10)(11)(12). Attempts to predict the future number of cases of vCJD, assuming exposure to bovine prions prior to the offal ban, have been uninformative because so few cases of vCJD have occurred (312)(313)(314).…”
mentioning
confidence: 99%
“…Epidemiologic studies designed to identify the source of the CJD infection were unable to identify any predisposing risk factors, although some geographic clusters were found (9)(10)(11)(12). Libyan Jews living in Israel developed CJD about 30 times more frequently than other Israelis (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No rural clusters were identified and there was little evidence for space-time clustering. In similar studies of CJD in England and Wales between 1970-1984, Cousens et al (1990 found no evidence of space-time clustering of dates and places at onset although they did find an excess of cases born in London. However, these authors warned that a number of statistically significant relationships in the earlier reports based on data for 1970--1979 were no longer significant when the data were extended to cover [1970][1971][1972][1973][1974][1975][1976][1977][1978][1979][1980][1981][1982][1983][1984].…”
Section: Does Temporal and Geographical Clustering Imply Acquired Aetmentioning
confidence: 88%